Major policy changes for primary care: potential lessons for the US New Model of family medicine from the quality and outcomes framework in the United Kingdom. - Lester, H; Hobbs, F (2007)
The Future of Family Medicine project in the United States has identified a series of core values and a New Model of practice for family medicine aiming to transform the health and health care of the nation. There are, however, few empirical examples of its effectiveness and acceptability in practice. Recent experiences of changes to primary health care in the United Kingdom (UK), particularly the introduction of the Quality and Outcomes Framework, which rewards practices for delivering evidence-based care, may provide some useful lessons for practitioners and policy makers as they implement aspects of the New Model. In this paper, the authors, who lead the Expert Review of the Quality and Outcomes Framework, critique the five characteristics of the New Model that offer the most relevant learning points for both health care systems and reflect on lessons for both clinicians and policy makers, highlighted by the experience of implementing policy change in the UK. They suggest that incremental implementation, underpinned by robust pilot data and in-depth understanding of the influence of motivation on performance, are key and conclude that sharing issues that have worked well, and less well, are important in helping both countries develop good quality patient care.